Optimalisasi Induksi Kalus Tebu (Saccharum officinarum L.) pada Media Murashige and Skoog dengan Penambahan Pikloram dan Kinetin - Nafia, Rosyida; Habibah, Noor Aini (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to analyze the effect of combined picloram and kinetin treatments on callus induction from young leaf roll explants of sugarcane variety Bululawang. The experiment was conducted using a completely randomized design with one factor consisting of 16 treatment combinations of picloram (0, 2, 4, and 6 ppm) and kinetin (0, 0.5, 1, and 1.5 ppm). The observed parameters included the time of callus initiation, percentage of explants forming callus, fresh weight, dry weight, and callus morphology. The results showed that the addition of picloram and kinetin combinations did not significantly affect the time of callus initiation but significantly increased the percentage of explants forming callus (averaging 86.72%) compared to the control (12.50%). The highest fresh and dry weights of callus were recorded at the treatment of 4 ppm picloram + 1 ppm kinetin, with a fresh weight of 0.4412 g and a dry weight of 0.0650 g. Callus morphology was predominantly compact in texture with a yellow to yellow-reddish color. The combination of picloram and kinetin effectively increased the percentage of callus induction, fresh weight, and dry weight of callus in sugarcane, indicating its potential application in tissue culture and secondary metabolite production.